National and Transnational Impacts of Terror on Hotel Stock Prices - Dlawar M. Hadi; Farman M. Ahmed (Polytechnic Journal)
This study aims to explore the sensitivity of hotel stock prices to national and transnational terrorist incidents that occur at the world’s top five tourist destinations. Event study analysis and the generalized sign test are the estimation techniques used in this study. Overall, hotel stocks were found to react differently to terrorist activities. U.S. hotel stocks were the most affected, and French hotel stocks were the least affected by domestic terrorist attacks. However, U.K. hotel stocks were the most influenced and Thai hotel stocks were the least influenced by transnational terrorist incidents. Based on the overall findings, several diversification, hedging, and speculation strategies are proposed for mitigating the effects of these influences to financial market stakeholders and hotel managers. This study recommends further studies to be conducted including various sectors to reveal how different sectors react to terrorist activities.